Participation - Charness, Gary; Dufwenberg, Martin (American Economic Review, 2011)
We show experimentally that whether and how communication achieves beneficial social outcomes in a hidden-information context depends crucially on whether low-talent agents can participate in a Pareto-improving outcome. Communication is effective (and pat terns of lies and truth quite systematic) when this is feasible, but otherwise completely ineffective. We examine the data in light of two potentially relevant behavioral models: cost-of-lying and guilt-from-blame. (JEL D82, D83, Z13)